Modern Monetary Theory: The Right Compass for Decision-Making - Dirk Ehnst (Intereconomics, 2022)
In the November/December 2021 issue of Intereconomics, Françoise Drumetz and Christian Pfister examine Modern Monetary Theory (MMT) and approach it from the policy consequences that would follow. This paper is a reply to Drumetz and Pfister. It restates the core of MMT and offers some suggestions for central banks. Theories are explanations of what we see, and MMT describes money creation and destruction. Hence, MMT cannot be and is not a political manifesto. In contrast to most other theories of money, MMT is falsifiable in its core statements, which are based on a balance sheet approach to macroeconomics. Since many central banks already educate the public about the creation of modern money through bank lending, it would be most welcome if they would do the same for the creation of modern money through government spending. Here, MMT and central bankers can find common ground to move forward and leave the theory of loanable funds and that of the money multiplier behind.
Keywords: E12; B52; B4; 330